Word equivalence of the bilingual storybook translation - Amalia, Ila (Diksi, 2022)
Equivalence is a very important factor and an inseparable part of a series of translation activities. Equivalence occurs when the linguistic units in the source language have the same meaning when it is transferred into the target language. This study aimed to describe (1) the translation difficulties in achieving word-level equivalence, and (2) the strategies in achieving word-level equivalence. The data sources were excerpts of words, phrases, and sentences from the bilingual storybook with the title Qonita dan Peternak Ayam - Qonita and The Chicken Breeder written by Setiawan G. Sasongko. Document observation was used as the data collection technique, meanwhile content analysis was used as the data analysis technique. The analysis of strategies and difficulties in translation were based on the theory of Baker (2011) and Newmark (1991). The results of the study indicated that the translation of bilingual storybook mostly used a word-by-word and free translation strategy to achieve word-level equivalence. The results of the analysis also revealed several types of difficulties in achieving the word-level equivalence. Those were differences in word forms, differences in the purpose and level of use of certain forms, cultural special concepts, and the absence of subordinate elements in the source language. Meanwhile, the strategies to overcome the difficulties found in achieving word-level equivalence were to eliminate certain words and to utilize more general words. Keywords: translation process, word equivalence, translation strategy, word translation, free translation